The effect of human serum and dentin powder alone or in combination on the antibacterial activity of sodium hypochlorite against Enterococcus faecalis. (January 2019) - Tong, Zhongchun; Zhang, Yanqing; Wei, Xi
Highlights: 10% HS showed the complete inhibition of 1% NaOCl against planktonic E. faecalis . 100 mg/mL DP did not completely inactivate antibacterial activity of NaOCl. HS showed more effect on the inactivation of NaOCl than DP. The low concentration of DP and HS showed an additive effect on action of NaOCl. DP and HS influenced the antibiofilm activity of 1% NaOCl against E. faecalis . Abstract: Objective: Dentin debris and organic components may affect the properties of intracanal irrigants. This study aimed to evaluate the effect of dentin powder (DP) and human serum (HS) on the antibacterial and antibiofilm activity of sodium hypochlorite (NaOCl) against Enterococcus faecalis . Design: DP from 100 to 6.25 mg/mL and HS from 10% to 0.3125% were interactively mixed and added into E. faecalis and 1% NaOCl solution. The live E. faecalis were counted after 1 min of contact. For biofilm testing, 7 days of E. faecalis biofilms were treated by 100 mg/mL DP and 10% HS alone or combination with 1% NaOCl solution for 1 min. Furthermore, after challenges, E. faecalis biofilms were stained with SYTO 9 and propidium iodide, and confocal laser scanning microscopy (CLSM) was used to determine the proportion of dead and live cells in the biofilm. Results: One hundred mg/mL DP or 10% HS alone showed the excellent inhibition of 1% NaOCl against planktonic E. faecalis, and the low concentration of DP and HS presented an additive inhibitory effect. The number of live bacteria in biofilms were significantly higher in the 1% NaOCl-treated group with DP or HS than without DP and HS ( p  <  0.05), and a higher percentage of dead bacteria was found in the challenge of NaOCl in the absence of DP and HS than in the presence of DP and HS. Conclusion: DP and HS generated the inhibition of antibacterial and antibiofilm activities of NaOCl, whereas the effect of HS was greater than DP.